Improving village information systems for sustainable development in Karawang Regency, Indonesia - Aryani, Lina; Kusumaningrum, Rastri (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
The village information system is a critical factor in rural development. The information system allows the government to accurately identify the direction of village development, in accordance with the needs and resources of the village. This research aims to examine and analyze the dimensions that affect the implementation and development of village information systems, as one of the village government's tools in realizing Sustainable Development Goals. This research used a case study approach with qualitative methods, where data was collected through documentation, observation, and interview techniques. The results identified many challenges in the implementation of village information systems in Karawang Regency, such as the lack of regulations at the local level, limited human resource capacity, less information technology infrastructure, and suboptimal performance of pilot applications. Based on these findings, strategic policy recommendations for improvement include formulating local regulations, investing in technology infrastructure, training and developing human resources. This research has positive implications for the application of village-based information systems in realizing the Village SDGs in Karawang.